Unveiling the Impact of Hallyu Phenomenon (Korean Wave) on the Adolescent Lifestyle in Indonesia - Dahroni, Dafit (LingPoet: Journal of Linguistics and Literary Research, 2024)
The Korean Wave, known as Hallyu, has had a significant impact on the lifestyle of teenagers in Indonesia, reflecting the popularity of South Korean culture in Asia. This research explores the influence of Hallyu on the lifestyle of teenagers, with a focus on the inspiration provided by Korean idols. The quantitative research method involved 152 respondents through an online questionnaire. These findings can serve as a foundation for education and business strategies that are more aligned with the cultural realities of Indonesian teenagers.